Ammothea bigibbosa (Arthropoda, Pycnogonida) a new species of the Antarctic Penninsula waters - Munilla, Tomás; Ramos, Ana (Polar Biology, 2005)
A new species Ammothea bigibbosa, collected with the Agassiz trawl in Margarita Bay at 517 m, is described, illustrated and compared with the similar species A. gordonae and A. adunca. Sí